Comparison of Long-term Investments in Single-family Housing with Stocks, and Fixed-income Securities Markets - Mohammadzadeh, Susan (2010)
The historical long-term volatility and return on investment in single-family dwellings was investigated and compared with investments in equity, bonds and T-bill markets. Total return index for equity and fixed-income security indices were obtained from available sources, of course, a proper index for measurement of long-term changes in house prices was unavailable. In an effort to measure the house price changes, a relatively homogeneous pool of houses in the downtown Toronto area was selected and its price tracked over the study period of 44 years. Inflation rate affects the return of investments in everything similarly therefore this was not considered in the calculations. Results of comparing the investment of cash in one's family home versus in other investment vehicles showed that the ratio of investment growth to its volatility for a single-family house exceeded the ratios for other investments by a large margin.